Report on Teaching Methodology Workshop - Safei, Su'aidi (2007)
Some forty UNISSA lecturers from Department of Arabic language, Syariah and Usuluddin, took part in the workshop, in which they were educated on various topics of teaching methods. Problems and obstacles on the part of the participants: i. Lecturers do not master the terminology and computer instructions in English, ii. Less practical use of computers in teaching and learning, iii. Easy to be theoretical but practical training even more important and requires time distribution.